The role of digital patient education in maternal health: A systematic review. Issue 3 (March 2022) - Schnitman, Gabriel; Wang, Tianci; Kundu, Shreenik; Turkdogan, Sena; Gotlieb, Raphael; How, Jeffrey; Gotlieb, Walter
Highlights: In clinical settings, digital patient education tools showed high effectiveness and patient satisfaction. - Main positive patient outcomes included knowledge gain, emotional benefits, and positive behavioral changes. The number of studies conducted each year increased steadily, reflecting the universalization of the internet and mobile devices. The most prevalent way to present maternal patient education material was on a website, with text and image illustrations. Patient education videos were also frequently used and produced the highest rate of positive patient outcomes. Abstract: Objective: To assess the recent trends, acceptability, and effectiveness of digital maternal patient education through summarizing the literature. Methods: Articles published in 2010–2020 on patient education, digital tools, and maternal health were searched on PubMed. Abstract and full texts were reviewed to identify eligible studies and extract key information. Results: Digital patient education studies covered various topics throughout pregnancy, with the greatest number of studies targeting the prenatal period. Among the 55 studies, 38 (69%) reported significant patient outcomes, with the main benefits of increased knowledge (83.3%), emotional benefits (73.7%), and behavioral changes (60.6%). The number of studies per year increased steadily over the past decade, with frequently utilized formats of texts with images (40%), SMS (30.9%), and videos (25.5%). Video produced the highest rate of positive patient outcomes; however, no statistical significance was found. Conclusion: Our study presented evidence supporting the high effectiveness and prevalence of digital tools in maternal patient education, and analyzed the content, platforms, and formats utilized by digital tools of the past decade. Practice implications: Digital tools are effective and feasible in conducting maternal patient education. No specific patient education format is found to be superior in improving patient's health outcomes.